Development and validation of a new finite element human head model: Yet another head model (YEAHM). Issue 1 (5th March 2018) - Fernandes, Fábio A.O.; Tchepel, Dmitri; Alves de Sousa, Ricardo J.; Ptak, Mariusz
Abstract : Purpose: Currently, there are some finite element head models developed by research groups all around the world. Nevertheless, the majority are not geometrically accurate. One of the problems is the brain geometry, which usually resembles a sphere. This may raise problems when reconstructing any event that involves brain kinematics, such as accidents, affecting the correct evaluation of resulting injuries. Thus, the purpose of this study is to develop a new finite element head model more accurate than the existing ones. Design/methodology/approach: In this work, a new and geometrically detailed finite element brain model is proposed. Special attention was given to sulci and gyri modelling, making this model more geometrically accurate than currently available ones. In addition, these brain features are important to predict specific injuries such as brain contusions, which usually involve the crowns of gyri. Findings: The model was validated against experimental data from impact tests on cadavers, comparing the intracranial pressure at frontal, parietal, occipital and posterior fossa regions. Originality/value: As this model is validated, it can be now used in accident reconstruction and injury evaluation and even as a design tool for protective head gear.